Host Antimicrobial Peptides: The Promise of New Treatment Strategies against Tuberculosis - Arranz-Trullén, Javier; Lu, Lu; Pulido, David; Bhakta, Sanjib; Boix, Ester (Frontiers in Immunology, 2017)
Tuberculosis (TB) continues to be a devastating infectious disease and remerges as a global health emergency due to an alarming rise of antimicrobial resistance to its treatment. Despite of the serious effort that has been applied to develop effective anti-tubercular chemotherapies, the potential of antimicrobial peptides (AMPs) remains underexploited. A large amount of literature is now accessible on the AMP mechanisms of action against a diversity of pathogens; nevertheless, research on their activity on mycobacteria is still scarce. In particular, there is an urgent need to integrate all available interdisciplinary strategies to eradicate extensively drug resistant Mycobacterium tuberculosis strains. In this context, we should not underestimate our endogenous antimicrobial proteins and peptides as ancient players of the human host defence system. We are confident that novel antibiotics based on human AMPs displaying a rapid and multifaceted mechanism, with reduced toxicity, should significantly contribute to reverse the tide of anti-mycobacterial drug resistance. In this review, we have provided an up to date perspective of the current research on AMPs to be applied in the fight against TB. A better understanding on the mechanisms of action of human endogenous peptides should ensure the basis for the best guided design of novel antitubercular chemotherapeutics.